The Impact of Perceived Organizational Politics on Peer Voice Endorsement: A Dual Mediation Model - Peiwen Qiu; Tingjing Chen; Liao Hu; Hao Zhou (Behavioral Sciences, 2025)
Peer voice endorsement, an emerging focus in voice research, is recognized for its important role in enhancing work efficiency. This study aims to examine the impact of perceived organizational politics on peer voice endorsement. It also explores the underlying mechanisms by developing a model based on the cognitive-affective personality system theory. Study data were collected in three waves from 226 full-time employees in China. The hypotheses were examined using SPSS 25.0 and the PROCESS macro. Empirical results indicate that perceived organizational politics negatively affects both psychological safety and affective commitment. Psychological safety and affective commitment also play a facilitating role in peer voice endorsement. Moreover, these two factors serve as mediators in the relationship between perceived organizational politics and peer voice endorsement. By highlighting the pivotal role of perceived organizational politics, this study offers valuable insights into its implications for peer voice endorsement. It further underscores the significance of psychological safety and affective commitment, demonstrating their essential function in cultivating a work environment that encourages peer voice endorsement.